Cocaine’s cerebrovascular vasoconstriction is associated with astrocytic Ca2+ increase in mice - Yanzuo Liu; Yueming Hua; Kicheon Park; Nora D. Volkow; Yingtian Pan; Congwu Du (Communications Biology, 2022)
Multimodal imaging of the mouse brain following acute cocaine application revealed that cocaine caused a biphasic calcium response in neurons, but not astrocytes, suggesting that these cells play different roles in mediating neurovascular coupling to cocaine.